Level of integration in current undergraduate curricula of two private-sector medical colleges in Karachi - Baig, Naila; Siddiqui, Faiza; Baig, Mirza Altamish Muhammad; Khursheed, Iram; Meah, Khubaib Muhammad Shamim (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2022)
Background: Diverse strategies are employed globally to integrate medical curricula. Nevertheless, a gap exists in assessing the role of medical instructors in meaningful integration. We developed and used a tool to explore the current level of integration, score medical instructors’ individual practices for integration, and investigate contextual elements minimizing integration.Methodology: This cross-sectional study, conducted in September-November-2020, used convenience-sampling. The study participants were basic-sciences and clinical instructors at two private-sector medical colleges in Karachi-Pakistan (with a response rate of 53.5%, n = 107). We validated a paper-based questionnaire through a pilot study on five participants. This tool with 11 close-ended questions on a 5-point Likert scale generated instructors’ integration scores, and six open-ended questions probed instructors’ perspectives.Results: The mean integration score was 37.4±6.7. Participants’ perspectives indicated a need for participation of clinical faculty in teaching initial undergraduate years, involving lecturers in curriculum meetings, and integration of assessment. The questionnaire Cronbach-alpha was 0.732 with satisfactory principal-component-analysis.Conclusion: Medical instructors facilitated integration mainly through concurrent timetabling of similar topics. Moreover, formal consultation through committee meetings, with discipline-based and integrated approaches complementing each other, were in practice to achieve curricular goals.